Estudo da variação horizontal das condições químicas, físicas e biológicas no reservatório de Itupararanga, Votorantim-SP e suas potenciais influências na toxicidade do sistema - Lira, Vivian Silva [UNESP] (2015)
This study aimed to analyze the limnological and ecotoxicological aspects in Itupararanga reservoir - Votorantim (SP) and their potential influences on the system toxicity, with emphasis on natural cyanobacterial blooms. Therefore, there were four samples in dry periods seeking a chemical, biological and toxicological approaches of surface water and sediment samples. In addition, the isolation and cultivation of the predominant cyanobacteria in the water samples. In order to assess the potential toxicity of strains and identify possible cianotoxins present in the reservoir's water. The results demonstrated the predominance of cyanobacteria compared to other phytoplankton groups in two study periods, markedly the domain of the species Cylindrospermopsis raciborskii, with the amount of cyanobacteria in violation of the CONAMA resolution 357/05. The ecotoxicological tests with superficial water and Ceriodaphnia dubia ascertained that caused acute toxicity in the first and third samples in the same collection site, and chronic toxicity earlier in the system in the first collection. Regarding the sediment samples taken in points 2 and 3 had acute toxicity in the first reporting year with high capacity to retain pollutants, which may be contributing to the installation of the system toxicity. Furthermore, the strains isolated from two species of cyanobacteria were proved to produce microcystin and saxitoxin. Subsequently, ecotoxicological assays with the isolated strains showed that same consistent concentrations in Brazilian law for potability (ordinance 2914/2011), these cyanotoxins can cause disturbances to environmental health. The reduction of the toxicity of microcystin and saxitoxin by means of ultrasound was efficient. Given the above, it is evident the possibility of compromising the quality of the water resources, which limits their multiple uses, considering both human consumption and the possibility of injury to the protection of ...